Response of Growth and Yield of Shallots (Allium cepa L.) in Dry Land on the Application of Smart K – Drip Fertigation - Nur Iman Muztahidin; Alfu Laila; Yessica C.N. Sihombing; Andi A. Fatmawaty; Nuniek Hermita (Faculty of Agriculture, Pattimura University, 2023)
This study aimed to determine the effect of various doses of Smart K-Drip Fertigation on the growth and yield of shallots (Allium cepa L.) in dry land. The field research was arranged in a Randomized Completely Block Design (RCBD) consisting of one factor with 4 replications. The treatments were Control (Conventional/without Smart K-Drip Fertigation), K50 (Smart K-Drip Fertigation with a K-fertilization dose of 50% of the recommendation), K75 (Smart K-Drip Fertigation with a K-fertilization dose of 75% of the recommendation), K100 (Smart K-Drip Fertigation with a K fertilizer dose of 100% of the recommendation), K125 (Smart K-Drip Fertigation with a K fertilizer dose of 125% of the recommendation), and K150 (Smart K-Drip Fertigation with a K fertilizer dose of 150% of the recommendation ). The results showed that the dose of Potassium (K) 75% with the application of Smart K-Drip Fertigation gave the best results on shallot growth and yield parameters, and showed that fertilization with drip fertigation was more efficient than conventional fertilization. In conclusion, it can be stated that the use of Potassium in shallots can be reduced by 25% by fertilizing with drip fertigation in dry land.